IMPROVING THE ABILITY TO CALCULATE ADDITION AND SUBRACTION THROUGH THE JARIMATIKA METHOD IN GRADE 1 STUDENTS - Robiatul Adewiyah; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
To be able to achieve educational goals, the teacher must apply a good approach and in accordance with the characteristics and needs of students. The background of the problem in this study is the low ability to calculate addition and subtraction in grade 1 sdn Kamal 3. This study aims to determine the effectiveness of the Jarimatika method in learning addition and subtraction and is expected to improve student achievement and make it easier for teachers to convey material in order to create a learning atmosphere that is conducive to learning pleasant. The research method used is Classroom Action Research which is carried out in collaboration between teachers and researchers. The results showed that there was an increase in student learning outcomes in calculating addition and subtraction using arithmetic in mathematics. So it can be concluded that the arithmetic learning method increases the speed of working on questions and understanding the material.